Evidence of climate variability from rainfall and temperature fluctuations in semi-arid region of the tropics - Umar, Da'u Abba; Ramli, Mohammad Firuz; Aris, Ahmad Zaharin; Jamil, Nor Rohaizah; Aderem, Adebayo Abel (Elsevier, 2019)
The pattern of rainfall and temperature behaviour in the Hadejia River Basin (HRB) has been assessed. The behaviour of rainfall and temperature have been used as proxies in detecting the presence of climate variability. Historical rainfall and temperature monthly data spanning thirty-six years (1980–2015) obtained from the Nigerian Meteorological Agency (NIMET) was used in this study. ANOVA and Mann-Kendall trend test was used for the data analysis. The ANOVA results showed significant variation in rainfall, maximum and minimum temperature between the stations. The Mann-Kendall trend test result shows an increasing trend in both rainfall and temperature in annual statistics, though statistically insignificant. However, the monthly trends result showed mixed results of both significant and insignificant as well as increasing and decreasing trends. The mean, standard deviation and the coefficient of variation were spatially interpolated using inverse distance weightage technique for easy comprehension. Even though the annual increasing trends result was statistically insignificant except for two out of the ten stations, it is still crucial for planning water-related activities and programs considering the sensitivity and fragility of the region to minor climatic variations.